Antibacterial Activities of Ethanol Extract of Jernang Resin (Daemonorops draco Blume) - Muhaimin Muhaimin; Indra L. Tarigan; Dyah M. Devy; Diah R. Gusti (Universitas Padjadjaran, 2021)
The resin compound is obtained from Jernang (Daemonorops draco blume), a plant that grows in the tropical rainforests of Indonesia. This study was undertaken to determine the antibacterial ability of ethanol extract of Jernang resin against both Salmonella typhi and Streptococcus mutans. The crude extract was prepared by soxhlet extraction in ethanol, is then fractionated vacuum liquid chromatography (VLC) with increasing solvent polarity starting from n-hexane (100%); n-hexane: ethyl acetate (80:20); ethyl acetate: methanol (40:60) up to methanol (100%) by. The antibacterial activity were evaluated using the disc diffusion method, these were compared with that of standards chloramphenicol as positive control and DMSO as a negative control. Determination of the antibacterial activity, we verified the diameter of inhibition of growth zone against Salmonella typhi at the variation of the extract concentration were 0.00mm/10ppm, 9.03mm/50ppm, 8.4mm/100ppm, 11.73mm/500ppm. These were compared with that of standards chloramphenicol (21.03mm/300ppm) and DMSO (0.00mm/300ppm). On the other hands, the diameter of inhibition of growth zone against Streptococcus mutans at the variation of the extract concentration were 9.33mm/50ppm, 9.83mm/75ppm, 10.67mm/100ppm, 11.5mm/125ppm, and 13.33mm/150ppm. These were compared with that of standards chloramphenicol (25.7mm/300ppm) and DMSO (0.00mm/300ppm). The ethanol extract of Jernang Resin exhibited antibacterial effects on Salmonella typhi and Streptococcus mutans, but these effects were less than chloramphenicol. The antibacterial effect increased with an increase in the concentration of the extract.